Negotiating Indigenous Peoples' Exit From Colonialism: The Case for an Integrative Approach. Issue 1 (January 2014) - Coyle, Michael
Abstract : New institutions of indigenous governance will be the product of negotiations, negotiations that will take place against a background of colonial structures and relationships. Having examined the challenges of structuring a negotiation process that takes due account of pre-existing cultural and power differences between the parties, the author analyzes the significance of their choice of negotiation strategy on the negotiation process and outcome. In particular, this paper reflects on the promise and limitations of the parties' adopting interest-based, or "integrative", negotiation strategies and the potential for fruitful entanglements between those strategies and indigenous diplomatic traditions.